Kesadaran Metakognitif Mahasiswa Melalui Pembelajaran Mandiri - Wachidatul Linda Yuhanna; Nuri Ati Ningsih (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
Metacognitive awareness is essential in learning, which includes knowledge about cognition and regulation about cognition. This study aims to 1) To know the average value of metacognitive awareness of biology education students which includes knowledge about cognition and regulation about cognition. 2) To know the percentage of student knowledge about cognition. 3) To know the percentage of student regulation about cognition. 4) To know the percentage of students metacognitive awareness. The instrument used is Metacognitive Awareness Inventory (MAI) developed by Schraw and Dennison (1994) which contains 52 questions with a score of 1 (true) and 0 (false). The results show that the mean value of metacognitive awareness is declarative knowledge (5,4); procedural knowledge (2,6); conditional knowledge (3.8); planning (4.9); information management strategy (6.4); understanding monitoring (4.8), search strategy (4.3) and evaluation (3.6). The percentage of knowledge about cognition of students with high (37.78%); medium (15.50%) and low (46.67%). The percentage of regulation about cognition of students with high (34.44%); medium (34.44%) and low (31.12%). The percentage of students metacognitive awareness with high (36.67%), medium (28.89%) and low (34.44%) so that there should be efforts to increase metacognitive awareness in biology education students.